"I feel really special and proud that I am bilingual": Exploring a second-generation Korean American bilingual adolescent's emotions and sense of belonging through family language policy. (April 2023) - Jo, Ahyea (Alice); Richardson, Stephanie; de Jong, Ester J.
Aims and objectives: The purpose of this exploratory case study is to contribute to the set of studies that center children's perspectives on their bilingual development, with a specific focus on their emotional connection within their linguistic family landscape. Methodology: This was a case study of a Korean transnational family in the United States and included both parents and their daughter. Data and analysis: Due to COVID-19 restrictions, semi-structured in-depth interviews and a language-mapping activity were conducted via ZOOM, recorded, and transcribed. DeDoose, a qualitative collaborative research tool, was used to conduct a thematic analysis. Findings and conclusion: Findings suggest that parents positioning bilingualism as a resource for communication and expression impacts a bilingual child's positive linguistic and socioemotional well-being. A strong sense of belonging was shaped through strong relationships with parents and family, engagement in diverse and inclusive spaces that valued multilingualism and multiculturalism, and by being given agency in one's own language choices. Originality: This study focuses on a Korean immigrant family and centers on the child's experiences. It provides a counter-narrative to the negative emotions parents and their children often express in extant family language policy (FLP) research. The study calls for FLP research to include a "multilingualism as a resource" orientation. Significance/implications: This case study provides the lens of multilingualism as a resource through FLP that has a different impact on the emotional dimensions of heritage language learning and maintenance.